Função social dos direitos autorais no âmbito dos direitos fundamentais : uma leitura constitucional das alterações propostas pelo Projeto de Lei 3.133/2012 às limitações aos direitos autorais sob uma perspectiva principiológica - Alencar, Mariése Garcia Costa Rodrigues de (2014)
The production of knowledge and the information were imposed, since the beginning, as necessary to human existence, implying in processes of social memory and transmission, as well, recognition of rights. Throughout history, restrictions on access to information were common, putting themselves at opposite ends those who possessed the copyright, or those to whom they were related, and those who would fit the right of information, which is a cornerstone of social inclusion and citizenship. In fact, there is a causal correlation between intellectual production and dissemination, as the search for knowledge is closely linked to the need for their disclosure and use for the benefit of man himself. In this sense, an intellectual or scientific discovery has meaning only when it fulfills its social function. The scope of this study is to examine, from the perspective of constitutional and contemporary conception of human rights, the counterpoint between the protection of copyright and its social function. Therefore, initially it is presented a retrospective of the assertion of human rights in history and their generations, highlighting the current characteristics of universality, indivisibility, interdependence and interrelatedness of human rights. Then it was performed a review about the positiveness of the rights inherent to the human person in the legal-constitutional states, including Brazil, distinguished human rights from fundamental rights. Marks of the law constitutionalization in Brazil were also investigated, with emphasis on the ideology of post-positivism, the normative force of the Constitution and constitutional interpretation. The copyright and its social function were also addressed, from the international point of view and from the Brazilian Constitution of 1988, with the presentation of the two strands of current protection of the rights of intellectual creators, the Anglo-American and the French. After, there was a study of the constitutionalization of copyright in Brazil, using the proportionality as the criterion to solve the apparent conflict between the rights of the individual author and their social function. Finally, it was performed a constitutional analysis of the law proposal n. 3133, of 2012, which intends to modify the current law that deals with this matter, in particular to analyze its principled structure and the limitations to the author s rights.